Strategi Bertahan Hidup Masyarakat Petani Pepaya di Pulau Birandang dalam Menghadapi Fluktuasi Pendapatan - Elizabeth, Elizabeth; Livhia Putri Hardiyanti; Rika Ruddaini; Widia Casandra Nasution; Victor Rafael Hutabarat; Resdati Resdati; Muhammad Ihsan (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
Income fluctuation is one of the common problems faced by farmers due to various factors, including seasonal changes, market price fluctuations, land ownership, and production costs. This condition is also experienced by papaya farmers in Pulau Birandang Village, Kampa District, Kampar Regency, where farming serves as the primary source of household income. This study aims to analyze the forms of income fluctuation experienced by papaya farmers and the survival strategies they employ to cope with unstable income conditions. The study used a qualitative approach with a descriptive method. Informants were selected purposively and consisted of five papaya farmers. Data were collected through observation, interviews, and documentation, and then analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results indicate that income fluctuations among papaya farmers are influenced by seasonal conditions, market price changes, land area, and production costs. To maintain household economic sustainability, farmers implement various survival strategies, including active strategies through seeking additional income sources, passive strategies through reducing household expenditures, and network strategies through utilizing social relationships with family members, neighbors, and the surrounding community. The findings suggest that survival strategies play an important role as an adaptive mechanism for farmers in dealing with economic uncertainty caused by income fluctuations.